A supply chain performance assessment model in multinational enterprises using foreign affiliates statistics - Antonio Frenda; Stefano D’Ottavi (Supply Chain Analytics, 2023)
With a globalized economy, traditional boundaries are becoming both unclear and uncertain, and it is necessary to analytically measure business globalization to estimate the results of the production activity of resident producer units. The value chains that have bound the world economy are now under new strain. This study presents an analysis of data relating to the activities carried out by a company in multinational territories. We study the distribution of the added value of companies and the relationship with their non-domestic activities for statistical purposes; the type of foreign affiliate known as a branch is considered a quasi-enterprise (Eurostat − Manual on Business Demography Statistics, 2007), resident in one country and controlled by a unit resident in another nation. We use two separate sources of sectoral information for a specific year (2019): Foreign Affiliates Statistics (FATS), covering activities of permanent establishments operating among Italian borders under foreign control, and outward FATS covering the activities of Italian branches abroad. Hence it can be difficult to untangle these complex chains of control; as we detail in this work, the integrated use of archives, statistical, administrative, and tax sources, as well as other information (company sites, profiling of the main multinational groups) allows to select the subset of companies potentially interested in the reality of foreign production a priori, to identify affiliates that are not constituting separate legal entities. This study can be used by public decision maker to highlight fiscal elusive strategies and estimate the real share of domestic and foreign (through stable organizations) production.